Utilization of Iron Filings as Partial Replacements for Sand in Self-Compacting Concrete - Olawale, Simon O.; Kareem , Mutiu A.; Muritala, Habeeb T.; Adebanjo , Abiola U.; Alabi , Olusegun O.; Olawuyi, Oluwole A.; Fadipe, Olusola O. (Tanzania Journal of Science, 2021)
The use of industrial by-products in concrete production is part of concerted efforts on the reduction of environmental hazards attributed to the mining of conventional aggregates. Consideration of iron filings (IF), a by-product from steel production process, is an environmentally friendly way of its disposal which is expected to yield economic concrete production. Six self-compacting concrete (SCC) mixes were made by partially substituting river sand with IF at 5%, 10%, 15%, and 20% and the mix without IF (0% IF) served as the control. The water-binder (w/b) ratio of 0.45 was adopted for all mixes. The fresh state properties of SCC evaluated include: filling ability determined using slump flow and T500 mm slump flow tests, passing ability determined using L-box test and segregation resistance determined using V-funnel tests. The strength properties of SCC considered were compressive and tensile strengths. All the SCC mixes met the fresh properties requirements for filling capacity, passing ability, and segregation resistance. The 28-day compressive and tensile strengths of SCC increased by 3.46% and 8.08%, respectively, with IF replacement up to 15% compared to the control SCC. However, there was reduction in compressive and tensile strengths of SCC with IF replacement beyond 15%. The strength properties of SCC is considerably enhanced with the addition of up to 15% IF. Hence, the optimum content of 15% IF is considered suitable as a replacement for river sand in SCC. Keywords: Self-compacting concrete; iron filings; fine aggregates; filling ability; passing ability.